Notice of the Priory of Beauly, Inverness-shire (Proceedings of the Society of Antiquaries of Scotland, 1869)
This article discusses the Priory Church at Beauly, the lives of the monks who lived there and what remains of the priory building. The author uses original documents to examine the genealogy of the de Bisset family, who granted lands and religious rites to the monastic order that founded the priory in the 13th century, as well as other members of the local nobility who were involved in the priory throughout the years. He concludes by describing the architecture of the priory and relating some of the local folklore about the building.